Trace metals and animal health: Interplay of the gut microbiota with iron, manganese, zinc, and copper - Pajarillo, Edward Alain B.; Lee, Eunsook; Kang, Dae-Kyung (Animal Nutrition, 2021)
Metals such as iron, manganese, copper, and zinc are recognized as essential trace elements. These trace metals play critical roles in development, growth, and metabolism, participating in various metabolic processes by acting as cofactors of enzymes or providing structural support to proteins. Deficiency or toxicity of these metals can impact human and animal health, giving rise to a number of metabolic and neurological disorders. Proper breakdown, absorption, and elimination of these trace metals is a tightly regulated process that requires crosstalk between the host and these micronutrients. The gut is a complex system that serves as the interface between these components, but other factors that contribute to this delicate interaction are not well understood. The gut is home to trillions of microorganisms and microbial genes (the gut microbiome) that can regulate the metabolism and transport of micronutrients and contribute to the bioavailability of trace metals through their assimilation from food sources or by competing with the host. Furthermore, deficiency or toxicity of these metals can modulate the gut microenvironment, including microbiota, nutrient availability, stress, and immunity. Thus, understanding the role of the gut microbiota in the metabolism of manganese, iron, copper, and zinc, as well as in heavy metal deficiencies and toxicities, and vice versa, may provide insight into developing improved or alternative therapeutic strategies to address emerging health concerns. This review describes the current understanding of how the gut microbiome and trace metals interact and affect host health, particularly in pigs.